Anti-Diabetic Activity of the Methanolic Extract of Blumea lacera DC (Asteraceae) in Alloxan-induced Diabetic Rats - Shahwar, Durre; Ullah, Saif; Ahmad, Mobasher; Ullah, Sami; Ahmad, Naeem (Asian Journal of Chemistry, 2011)
Anti-diabetic activity of the methanolic extract of B. lacera was studied in alloxan-induced (150 mg/kg) in diabetic rats, after oral adminis-tration, at doses of 125, 250, 500, 750 and 1000 mg/ kg. A long term hypoglycemic activity of methanolic extract of B. lacera was also performed. Biochemical parameters studied included triglyceride, total cholesterol, high density lipoprotein, low density lipoprotein and very low density lipoprotein. Fasting blood glucose and biochemical parameters were studied on the day 0, 7 and 14. The data was compared statistically by employing one way analysis of variance. Oral administration of methanolic extract (500 mg/kg) to alloxaninduced diabetic rats for 14 days duration restored blood glucose levels to normal values. The present study clearly indicated a significant antidiabetic activity of the methanolic extract of B. lacera, thus making the plant B. lacera more valuable in treating diabetes.